Analisis Statistik Asuhan Kesehatan Dalam Meningkatkan Jumlah Kunjungan Pasien - Afira Putri Khairiyah (Iris Journal of Health Information Management, 2022)
Health care statistics are useful as a basis for comparing hospital performance in the past with current and future plans, especially on the level of patient satisfaction. The purpose of this study was to determine the statistical benefits of health care in increasing the number of patient visits at RSI Ibnu Sina Padang. The data processed is secondary data of inpatients at RSI Ibnu Sina Padang in the period 1 March - 30 April 2019 data obtained from 993 patients with 124 beds, then data processing was carried out using the Microsoft Excel application program. Statistical processing was analyzed and presented in the form of tables and graphs by Barber Johnson. The BOR result is 31.90%, it is not efficient because the BOR efficiency is 60–85%. BTR is 8.01 times, inefficient because the period required for efficient BTR calculation is one year, BTR efficiency is 40–50 times one year. IT 5 days, not efficient because of the efficiency of 1 – 3 days. ALOS of 3.14 days or 3 days, is not efficient because of the efficiency of 6 – 9 days. RL4a reports, the highest age group is 45-64 years old with a total of 302 patients. The highest gender was female 666 patients, and male 327 patients, based on the disposition of life 985 patients, and 8 patients died. The highest diagnosis was non-insulin-dependent diabetes mellitus without complications with code E11.9 totaling 38 diagnoses. The main diagnosis based on defecation on ICD-10, the highest diagnosis was Chapter II (Neoplasm) with 13.70% totaling 136 diagnoses. The main diagnosis according to the highest DTD with a DTD code of 242.9 (Complications of pregnancy and childbirth) was 47 diagnoses. The highest procedure is X-ray ches with a code of 87.44 with a total of 49 codes. The distribution of patients based on the area the most was Padang City with a total of 817 patients.